Short Communication: Behavioural Adaptations in Mating Patterns of Timor Deer (Cervus timorensis) in Captive Conditions in Kediri Facilities, East Java - Putri, Ardyah Ramadhina Irsanti; Ciptadi, Gatot; Fahmi, Mohammad Bachtiar (Jurnal Sain Peternakan Indonesia, 2025)
The Timor deer (Cervus timorensis), an endemic species of Indonesia, faces a severe population decline caused by habitat degradation, illegal hunting, and limited conservation initiatives. Captive breeding represents a strategic measure to enhance reproductive performance and ensure species persistence. This study examined the mating behaviour of Timor deer at the Brigif-16/Wira Yudha facility, Kediri, emphasising the effects of environmental conditions, social dynamics, and enclosure management. A total of 15 adult males and 40 adult females were monitored over two months using scan sampling across four daily periods (06:00–12:00, 12:00–15:00, 15:00–18:00, and 18:00–24:00). Results indicated that mating-related behaviors accounted for 18.7% of total activities, with the highest occurrence in the morning (06:00–12:00; 42.5% of mating events). Male-to-male competition represented 11.3% of all observations, also peaking in the morning, while female affiliative behaviours reached 15.8% during the same period. Activity levels declined sharply during midday heat (12:00–15:00; 8.6% of mating events) and in the evening (18:00–24:00; 6.2%), indicating strong environmental influence. Compared with wild populations, captive deer exhibited more clustered behavioural patterns, likely due to controlled feeding schedules, enclosure design, and the absence of predators. These findings suggest that reproductive monitoring and interventions should prioritise morning sessions when mating and social interactions are most frequent. Management practices that consider natural rhythms, minimise midday heat stress, and optimise social grouping can significantly improve welfare and reproductive output. Beyond practical applications, this study contributes to the understanding of polygynous cervid reproductive ecology under captive conditions. The insights gained provide a framework for refining conservation breeding strategies not only for Timor deer but also for other threatened ungulates facing similar challenges.